2021
DOI: 10.1002/1878-0261.12910
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomics reveal the intratumoral landscape of infiltrated T‐cell subpopulations in oral squamous cell carcinoma

Abstract: Systematic analysis of tumor‐infiltrating lymphocytes is essential for the development of new cancer treatments and the prediction of clinical responses to immunotherapy. Immunomodulatory drugs are used for the treatment of oral squamous cell carcinoma (OSCC), depending on immune infiltration profiles of the tumor microenvironment. In this study, we isolated 11,866 single T cells from tumors and paired adjacent normal tissues of three patients with OSCC. Using single‐cell RNA sequencing, we identified 14 disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 67 publications
(77 reference statements)
2
23
0
1
Order By: Relevance
“…Among these clusters, cluster B was characterized by a higher expression level of m1A regulators and poorer prognosis. Immune, stromal, and ESTIMATE scores were markedly lower and tumor purity was higher in cluster B than those in clusters A and C. Substantial studies have indicated that the crucial role of TILs in the TIME of OSCC, which could affect or predict the treatment effect of ICIs [ 33 , 34 , 35 ]. High CD8-positive T cell expression among TILs is thought to be associated with a better OS outcome in HNSCC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these clusters, cluster B was characterized by a higher expression level of m1A regulators and poorer prognosis. Immune, stromal, and ESTIMATE scores were markedly lower and tumor purity was higher in cluster B than those in clusters A and C. Substantial studies have indicated that the crucial role of TILs in the TIME of OSCC, which could affect or predict the treatment effect of ICIs [ 33 , 34 , 35 ]. High CD8-positive T cell expression among TILs is thought to be associated with a better OS outcome in HNSCC [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ssGSEA analysis results showed that compared with cluster A, cluster B had lower immune activity in the above immune cell types, which suggests a more suppressive state of the TIME in cluster B. Recent reports have demonstrated that TILs widely affect the TIME in OSCC ( Boxberg et al, 2019 ) ( Quan et al, 2016 ) ( Chen J. et al, 2021 ). Among the TILs, high expression of CD8 + T cells has been proven to be related to a better prognosis in HNSCC ( Nakano et al, 2001 ).…”
Section: Discussionmentioning
confidence: 65%
“…The enhanced activity of CD8 + T cells was also associated with a reduction in the expression of TIM3 (T-cell immunoglobulin domain and mucin domain 3) and PD-1, which are markers of dysfunction and exhaustion of CD8 + T cells (Supplementary Fig. S2F) (32)(33)(34).…”
Section: Resultsmentioning
confidence: 96%